Ficción televisiva en YouTube, eduentretenimiento para Educación Integral en Sexualidad en tiempos de pandemia - Batista Rangel, Adriana Carolina (2024)
This paper shows the results of the use of television fiction for Comprehensive Sexuality Education in times of confinement. A post-test adapting the "Questionnaire for the evaluation of Knowledge, Attitudes and Practices related to sexual activity, HIV, VTP and GBV" was applied to 80 adolescents (15-17 years old), 41 had watched on YouTube 20 chapters of the fiction series on sexual and reproductive human rights and sexual and reproductive health "Revela2" and 39 constituted the control group. When comparing means by groups, significant differences were found. The intervention group had greater knowledge about HIV, more favorable attitudes towards the use of the emergency pill, more favorable attitudes towards sexual diversity, and greater perception of self-efficacy in making decisions about romantic and sexual relationships. The control group had more favorable attitudes towards adolescent sex, condom use and early HIV diagnosis.